2015
DOI: 10.1021/acs.joc.5b00825
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Promoted Oxidative Arylation of Vinyl Arenes to 2-Aryl Acetophenones without Irradiation at Room Temperature under Aerobic Conditions

Abstract: A convenient and general protocol for oxidative arylation of vinyl arenes by aryl radicals generated in situ from arene diazonium fluoroborates promoted by ascorbic acid in air at room temperature has been developed in the absence of any additive and visible light irradiation. A series of diversely substituted 2-aryl acetophenones have been obtained in good yields by this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Selected examples illustrating the implementation of this strategy are: (a) the αarylation of methyl ketones promoted by stoichiometric amounts of KOAc [13] (Scheme 1a); (b) the visible-light induced transformation with [Ru(bpy)3] 2+ as photocatalyst [14] (Scheme 1b); and (c) the use of hydrazines as organocatalysts [15] (Scheme 1c). Closely related methods for the oxidative arylation of vinyl arenes with aryl diazonium salts have also been developed, employing stoichiometric amounts of ascorbic acid as promoter [16] or visiblelight photoredox catalysis [17] . However, the latter strategy is limited to the synthesis of 2arylacetophenones, while benzyl alkyl ketones are not accessible.…”
Section: Introductionmentioning
confidence: 99%
“…Selected examples illustrating the implementation of this strategy are: (a) the αarylation of methyl ketones promoted by stoichiometric amounts of KOAc [13] (Scheme 1a); (b) the visible-light induced transformation with [Ru(bpy)3] 2+ as photocatalyst [14] (Scheme 1b); and (c) the use of hydrazines as organocatalysts [15] (Scheme 1c). Closely related methods for the oxidative arylation of vinyl arenes with aryl diazonium salts have also been developed, employing stoichiometric amounts of ascorbic acid as promoter [16] or visiblelight photoredox catalysis [17] . However, the latter strategy is limited to the synthesis of 2arylacetophenones, while benzyl alkyl ketones are not accessible.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the utilization of organic initiators for generation of aryl radicals from aryl diazonium salts has received increasing attention . For example, Carrillo and co‐workers reported that ascorbic acid can act as an appropriate initiator in intermolecular C−H arylation of arenes with anilines . In addition, iodide, benzoyl peroxide (BPO), and porphyrin have been identified as efficient initiators to generate aryl radicals from aryl diazonium salts.…”
Section: Methodsmentioning
confidence: 99%
“…Major drawbacks of hazardous solvent incorporate their volatile nature, pyrophoric property and poor recovery and the metal catalyst is not good for our environment and also it leads to metal contamination at the end of the reaction. Solvent free synthesis has gained ground these days and has been used for few transformations . However, solvent plays a prime part in organic reactions by providing a homogeneous mixture and enhancing molecular contacts.…”
Section: Introductionmentioning
confidence: 99%